Characteristics of Smallholder Cereal Farmers and Influence on Drought Adaptations in Makueni County, Kenya - Jackob Haywood Ondiko; Amon Mwangi Karanja; Humphreys Were Obulinji; Kennedy Nyabuti Ondimu (Annals of Arid Zone, 2025)
Characteristics of smallholder cereal farmers are key factors influencing adoption of community based drought adaptations and indigenous knowledge in drought-prone arid and semi-Arid Lands globally. Increasing frequency and severity of drought experienced in drylands is a major challenge to rain-fed cereal production in Africa. Kenya experiences frequent droughts which influence levels of vulnerability of the smallholder cereal farmers in arid and semi-Arid Lands that cover 80% of the surface area in the country. Frequent droughts and adverse pedo-climatic conditions in Makueni County in Kenya, influence cereal production, consequently, food security. This study evaluated the influence of characteristics of smallholder cereal farmers on adoption of drought adaptation techniques in Makueni County, Kenya. The study adopted explanatory sequential mixed methods research design. The study analysed the household data from a sample of 225 participants. More females than males adapted to droughts through use of indigenous knowledge including drought monitoring and prediction (61%), bio-control of weeds (57%), seed preservation (55%), use of farm manure (54%), supplementary irrigation (51%) and early planting of seeds (51%). Frequent droughts in Makueni County resulted in adoption of small farm sizes where 60%, 43% and 42% of the cereal farmers produced between 1 to 10 bags of maize, sorghum and finger millet, respectively. Information and data generated by this study is expected to result in improvement in drought adaptation policy formulation and drought adaptation capacity development among the smallholder cereal farmers. These efforts will result in improvement in food production and security in Arid and Semi-Arid Lands in Kenya. This study recommends studies on sustainable drought management practices in Arid and Semi-Arid Lands in Kenya.